The pattern and risk factors associated with adverse drug reactions induced by Reteplase in patients with acute ST-elevation myocardial infarction: The first report from Iranian population - Naser Aslanabadi; Naser Safaie; Faezeh Shadfar; Mohammad Reza Taban-Sadeghi; Hossein Feizpour; Simin Ozar Mashayekhi; Hadi Hamishehkar; Naser Khezerlou Aghdam; Samaneh Dousti; Hossein Namdar; Taher Entezari-Maleki (Wolters Kluwer Medknow Publications, 2015)
Objective: Acute myocardial infarction (AMI) is one of the main leading causes of mortality and morbidity. Reteplase is a fibrin-specific thrombolytic which is used in the treatment of AMI. There is a limited number of studies reporting the postmarketing adverse drug reactions (ADRs) induced by reteplase. This study was aimed to examine the reteplase pattern of ADR and its associated risk factors in patients with acute ST-elevation myocardial infarction. Methods: A cross-sectional, prospective study in an 8-month period was done at the University affiliated referral cardiovascular center. The Naranjo probability scale and World Health Organization criteria for severity of ADRs were used for assessing the ADRs. The linear regression and logistic regression tests were used to evaluate the correlation between ADRs and risk factors. Findings: The all 20 patients who received reteplase during the study period were entered. The majority of patients (n = 17) experienced at least one ADR. The results showed that the incidence of ADRs was mainly associated with gender and age, and the number of ADRs was associated with the history of diabetes and taking anti-diabetic agents. The gender was the main predictor in the occurrence of ADRs (odds ratio: 32, 95% confidence interval: 1.38-737.45; P = 0.030). Conclusion: The results showed that gender, age, diabetes mellitus, and using of anti-diabetes medications are the risk factors associated with the incidence of ADRs by reteplase.